2022
DOI: 10.1155/2022/8538700
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural and Functional Abnormalities of Hippocampus in Classical Trigeminal Neuralgia: A Combination of DTI and fMRI Study

Abstract: Purpose. Diffusion tensor imaging (DTI) and resting-state functional magnetic resonance imaging (rs-fMRI) were applied to speculate the altered structural and functional abnormalities within the hippocampus in classical trigeminal neuralgia (CTN) patients by detecting the alteration of apparent diffusion coefficient (ADC), fractional anisotropy (FA), and regional homogeneity (ReHo). Patients and Methods. Multimodal MRI dataset (DTI and fMRI) and clinical indices (pain and neuropsychological scores) were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…This indicated that there is a clear correlation between cognitive dysfunction and hippocampal functional and structural dysfunction in classical trigeminal neuralgia patients. Strong evidence has been provided showing that pain depends on the activation of mechanisms in higher brain centers that control emotions and generate emotional recognition (Tan et al, 2022 ). In addition, some researchers have used fMRI and DTI techniques to propose a skeleton-based method for WM functional analysis, which achieves voxel-based function–structure coupling by projecting fMRI signals onto the skeleton in WM.…”
Section: Voxel-wise Structure–function Couplingmentioning
confidence: 99%
“…This indicated that there is a clear correlation between cognitive dysfunction and hippocampal functional and structural dysfunction in classical trigeminal neuralgia patients. Strong evidence has been provided showing that pain depends on the activation of mechanisms in higher brain centers that control emotions and generate emotional recognition (Tan et al, 2022 ). In addition, some researchers have used fMRI and DTI techniques to propose a skeleton-based method for WM functional analysis, which achieves voxel-based function–structure coupling by projecting fMRI signals onto the skeleton in WM.…”
Section: Voxel-wise Structure–function Couplingmentioning
confidence: 99%